Anaïs Mitchell. [compact disc] - Mitchell, Anaïs (BMG US, 2022)
In 2006, Anais Mitchell began work on what would become the Tony and Grammy Award winning musical phenomenon Hadestown. Now, she returns with her first solo album since 2012. This includes collaborations with Bon Iver and The National.